2011
DOI: 10.1080/13803395.2010.535505
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Assessment Battery (FAB) is a simple tool for detecting executive deficits in chronic cannabis users

Abstract: This study examined effects of cannabis in executive functioning and showed evidence that the FAB is sensitive to detect EF deficits in early abstinent chronic cannabis users. Clinical significance of these findings remains to be investigated in further longitudinal studies. FAB may be useful as a screening instrument to evaluate the necessity for a complete neuropsychological assessment in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Solowij et al 11 found that information processing evaluated by paced auditory serial addition test was worse in long-term cannabis users than in short-term users or no users. Frontal Assessment Test, a neurocognitive function test, showed worse performance of cannabis users when compared to The changes of the cognitive and psychomotor functions in the chronic cannabis users after a month of remission controls 39 . AMIPB-A and AMIPB-B, tests for evaluating information processing, assess working memory, attention, sustained attention, comparison, which are mainly the functions of premotor frontal region 28,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Solowij et al 11 found that information processing evaluated by paced auditory serial addition test was worse in long-term cannabis users than in short-term users or no users. Frontal Assessment Test, a neurocognitive function test, showed worse performance of cannabis users when compared to The changes of the cognitive and psychomotor functions in the chronic cannabis users after a month of remission controls 39 . AMIPB-A and AMIPB-B, tests for evaluating information processing, assess working memory, attention, sustained attention, comparison, which are mainly the functions of premotor frontal region 28,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Impaired performance may depend on extent of prior exposure, route of administration, dose delivered, and blood cannabinoid concentrations at baseline and after dosing (89). With regard to the chronic effects of cannabis, numerous studies reported null findings in case-control comparisons (46,54,66,81,95,98,110,111), whereas several others found cannabis-related deficits in heavy users (53,78,83,112), including adolescents (113), early-onset but not late-onset adult users (114), and older users (57), and associated with persistent use in a longitudinal study (60). Impaired executive function was evident despite intact performance on other cognitive tasks (48,82) and associated with self-reported problems related to cannabis use (115).…”
Section: Executive Functionmentioning
confidence: 99%
“…Reports indicate that cannabis users, and particularly those with CUDs, may be at increased risk for mortality [9,10], yet other studies present conflicting findings [11]. In addition, CUDs may be associated with deficits in cognitive functions such as executive functions, working memory and both immediate and delayed memory [12][13][14][15]. The evidence regarding the extent to which these deficits improve during abstinence is conflicting [16,17].…”
Section: Introductionmentioning
confidence: 94%